2012
DOI: 10.1177/0193723512455919
|View full text |Cite
|
Sign up to set email alerts
|

“The Love of My Life”

Abstract: Pope, S. (2013) 'The love of my life : the meaning and importance of sport for female fans.', Journal of sport and social issues., 37 (2). pp. 176-195. Further information on publisher's website:http://dx.doi.org/10.1177/0193723512455919Publisher's copyright statement:The nal de nitive version of this article has been published in the Journal of Sport and Social Issues, 37/2, 2013 c SAGE Publications Ltd at the Journal of Sport and Social Issues page: http://jss.sagepub.com/content/37/2/176 on SAGE Journals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(14 citation statements)
references
References 21 publications
1
9
0
4
Order By: Relevance
“…The importance of feeling part of a community was emphasized by most of the participants in this study, as well as in previous research (see : Crolley & Long, 2001;Pope, 2010Pope, , 2013. However, it is clear that the concept of the collective has limits, and belonging in the community of sports fans is not bestowed to all fans equally.…”
Section: Discussionsupporting
confidence: 73%
“…The importance of feeling part of a community was emphasized by most of the participants in this study, as well as in previous research (see : Crolley & Long, 2001;Pope, 2010Pope, , 2013. However, it is clear that the concept of the collective has limits, and belonging in the community of sports fans is not bestowed to all fans equally.…”
Section: Discussionsupporting
confidence: 73%
“…She found that some female fans rejected women who performed conventional femininity on the grounds that they did not 'do fandom properly'. 43 Women and girls who participate in football also comply with dominant notions of femininity to construct a legitimate female identity. 44 At the same time, there are also studies that illustrate women rejecting a feminine identity in favour of an athletic identity.…”
Section: Sexism In Footballmentioning
confidence: 99%
“…12 Such findings are echoed by Pope, who theoretically unpacks the varying levels of engagement and diversity of females as sports fans of football and rugby union in the East Midlands city of Leicester. 13 However, just as there are few sporting ethnographies conducted by male researchers who acknowledge -or make visible -their own maleness, Jones and Pope appear to have overlooked the 'self' as a gendered subject in their own research. 14 Both authors discussed that females perform fandom with the knowledge that, to some male fans, their gender makes them inauthentic.…”
mentioning
confidence: 99%
“…Most literature on sports fans is male centred, focused on hooligan ethnographies. 22 One of the consequences of the hyper-masculine nature of football hooliganism and football culture generally is that male researchers have and continue to dominate the field of study. 23 Perhaps this is because the practice of conducting observational research on football 'hooligans' was deemed only appropriate for male sociologists.…”
mentioning
confidence: 99%